Left Ventricular Assist Device (LVAD) Implantation and Renal Dysfunction - Assem Nogaibayeva; Bagdat Sultanova; Myrzabek Makhmutov (National Scientific Medical Center, 2018)
Pathophysiological, pathomorphological and functional changes in the kidneys after left ventricular assist device implantation have not yet been fully understood and represent an actual problem of our time. Changes in renal function following left ventricular assist device implantation have been disclosed in many studies with inconsistent results. Some studies have shown that patients with renal dysfunction after left ventricular assist device implantation had worse outcomes, despite stabilization or even improvement of kidney function during the postoperative period, other studies have shown the progression of chronic kidney disease requiring renal replacement therapy.